The complete Chloroplast genome of Stachys geobombycis and comparative analysis with related Stachys species - Ru Wang; Zheng Lan; Yongjian Luo; Zhijun Deng (Scientific Reports, 2024)
Abstract Herb genomics, at the forefront of traditional Chinese medicine research, combines genomics with traditional practices, facilitating the scientific validation of ancient remedies. This integration enhances public understanding of traditional Chinese medicine’s efficacy and broadens its scope in modern healthcare. Stachys species encompass annual or perennial herbs or small shrubs, exhibiting simple petiolate or sessile leaves. Despite their wide-ranging applications across various fields, molecular data have been lacking, hindering the precise identification and taxonomic elucidation of Stachys species. To address this gap, we assembled the complete chloroplast (CP) genome of Stachys geobombycis and conducted reannotation and comparative analysis of seven additional species within the Stachys genus. The findings demonstrate that the CP genomes of these species exhibit quadripartite structures, with lengths ranging from 14,523 to 150,599 bp. Overall, the genome structure remains relatively conserved, hosting 131 annotated genes, including 87 protein coding genes, 36 tRNA genes, and 8 rRNA genes. Additionally, 78 to 98 SSRs and long repeat sequences were detected , and notably, 6 highly variable regions were identified as potential molecular markers in the CP genome through sequence alignment. Phylogenetic analysis based on Bayesian inference and maximum likelihood methods strongly supported the phylogenetic position of the genus Stachys as a member of Stachydeae tribe. Overall, this comprehensive bioinformatics study of Stachys CP genomes lays the groundwork for phylogenetic classification, plant identification, genetic engineering, evolutionary studies, and breeding research concerning medicinal plants within the Stachys genus.